Factors influencing place of delivery: Evidence from three south-Asian countries. - Md Ashfikur Rahman; Muhammad Aziz Rahman; Lal B Rawal; Mohan Paudel; Md Hasan Howlader; Bayezid Khan; Tanjim Siddiquee; Abdur Rahman; Apurbo Sarkar; Md Sazedur Rahman; Roslin Botlero; Sheikh Mohammed Shariful Islam (PLoS ONE)
Background High maternal mortality is still a significant public health challenge in many countries of the South-Asian region. The majority of maternal deaths occur due to pregnancy and delivery-related complications, which can mostly be prevented by safe facility delivery. Due to the paucity of existing evidence, our study aimed to examine the factors associated with place of delivery, including women's preferences for such in three selected South-Asian countries. Methods We extracted data from the most recent demographic and health surveys (DHS) conducted in Bangladesh (2014), Nepal (2016), and Pakistan (2017-18) and analyzed to identify the association between the outcome variable and socio-demographic characteristics. A total of 16,429 women from Bangladesh (4278; mean age 24.57 years), Nepal (3962; mean age 26.35 years), and Pakistan (8189; mean age 29.57 years) were included in this study. Following descriptive analyses, bivariate and multivariate logistic regressions were conducted. Results Overall, the prevalence of facility-based delivery was 40%, 62%, and 69% in Bangladesh, Nepal, and Pakistan, respectively. Inequity in utilizing facility-based delivery was observed for women in the highest wealth quintile. Participants from Urban areas, educated, middle and upper household economic status, and with high antenatal care (ANC) visits were significantly associated with facility-based delivery in all three countries. Interestingly, watching TV was also found as a strong determinant for facility-based delivery in Bangladesh (aOR = 1.31, 95% CI:1.09-1.56, P = 0.003), Nepal (aOR = 1.42, 95% CI:1.20-1.67, P<0.001) and Pakistan (aOR = 1.17, 95% CI: 1.03-1.32, P = 0.013). Higher education of husband was a significant predictor for facility delivery in Bangladesh (aOR = 1.73, 95% CI:1.27-2.35, P = 0.001) and Pakistan (aOR = 1.19, 95% CI: 0.99-1.43, P = 0.065); husband's occupation was also a significant factor in Bangladesh (aOR = 1.30, 95% CI:1.04-1.61, P = 0.020) and Nepal (aOR = 1.26, 95% CI:1.01-1.58, P = 0.041). Conclusion Our findings suggest that the educational status of both women and their husbands, household economic situation, and the number of ANC visits influenced the place of delivery. There is an urgent need to promote facility delivery by building more birthing facilities, training and deployment of skilled birth attendants in rural and hard-to-reach areas, ensuring compulsory female education for all women, encouraging more ANC visits, and providing financial incentives for facility deliveries. There is a need to promote facility delivery by encouraging health facility visits through utilizing social networks and continuing mass media campaigns. Ensuring adequate Government funding for free maternal and newborn health care and local community involvement is crucial for reducing maternal and neonatal mortality and achieving sustainable development goals in this region.